Implementasi Vicarious learning Dalam Menanamkan Nilai-Nilai Islami Pada Siswa Berkebutuhan Khusus - Nisa, Ummu Khairin; Afandi, Nur Kholik (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research was motivated by the behavior of students with special needs that did not reflect Islamic values, such as going in and out of class without permission, not focusing while studying, using harsh language, shouting during the learning process and so on. The aim of this research is find out how vicarious learning is implemented in instilling Islamic values in students with special needs . The research method used is qualitative descriptive. The results of the research show that instilling Islamic values, especially in children with special needs, is, firstly, the implementation of dhuha and noon prayers in congregation. Second, reciting the Koran. Third, the Friday charity program. Fourth, starting activities with prayer. Lastly, apologizing when making mistakes. Students with special needs at SD Muhammadiyah 3 are able to say sorry when they realize their mistake, even though they sometimes forget and need to be reminded.